The Influence of Work Discipline on Employee Performance at the Department of Population and Civil Registration of Buru Selatan Regency - Robiwalla, Riksan; Papilaya, Josef; Louhenapessy, William George M (JENDELA PENGETAHUAN, 2025)
This study examines work discipline's effect on employee performance at the Department of Population and Civil Registration of Buru Selatan Regency. The research employed a quantitative approach through a survey involving 35 respondents selected using purposive sampling. The primary instrument, a questionnaire measuring work discipline and employee performance, was tested for validity and reliability before use. The results of the simple linear regression analysis show that work discipline has a positive and significant impact on employee performance, with a regression coefficient of 0.611. Additionally, hypothesis testing yielded a t-value of 3.976 with a significance level of 0.000, indicating that work discipline significantly contributes to performance improvement. The R² value of 0.668 indicates that 66.8% of the variation in employee performance can be explained by work discipline, while other factors influence the rest. These findings emphasize the importance of work discipline in improving employee performance, and management should focus on discipline management to achieve higher effectiveness